The Influence of Intellectual Capital in Enhancing Sharia Performance in Islamic Banks with ESG as a Mediating Variable (A Study of Islamic Banks in Asia) - Khanifah Khanifah; Abdul Rohman; Jaka Isgiyarta (PT. Publikasiku Academic Solution, 2026)
Ideally, Islamic banks require a distinct performance assessment methodology from conventional banks due to transcendent elements. The deconstruction of sharia performance employed the epistemological procedure of the burhani mindset, involving logical analysis of qauliyah and qauniyah verses aligned with sharia purposes, yielding a sharia performance measure. In the IT era, human resource optimization and ESG practices drive company performance. This quantitative study examined intellectual capital's effect on improving sharia performance in Islamic banks, with ESG as mediator. Using purposive sampling, it gathered 126 observations from 18 Islamic commercial banks across eight Asian countries (2017–2023). Data from official websites and Bloomberg were analyzed via path analysis. Findings: Intellectual capital negatively affected sharia performance and ESG, though long-term investments eventually boost environmental awareness and sharia compliance. ESG positively influenced sharia performance, aligning maqashid sharia with SDGs. ESG partially mediated the intellectual capital–sharia performance relationship, with the indirect path lower yet significant compared to the direct path.